Pengetahuan Masyarakat Mengenai Penyakit Kecacingan di Desa Sungai Madang Kecamatan Sungai Tabuk Kab Banjar Kalimantan Selatan - isnaini isnaini; Lisda Hayatie; Zulfa Emelda (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2022)
Sungai Madang Village is a village located on the banks of the Tabuk river. This village is located in Sungai Tabuk District, Banjar Regency, South Kalimantan. The location of the village which is on the edge of the river and the many tributaries that surround the village of Sungai Madang make this village at risk of worm disease. This study aims to determine the level of public knowledge of helminthiasis and the use of worm medicine. The method used is the interview technique. The data obtained will be described. The profile of respondents as much as 31.25% are early elderly, 81.25% are women and 93.75% are married. The results of the survey show that 75% of respondents do not know about helminthiasis and they cannot mention the characteristics of helminthiasis. Profile of respondents who know about helminthiasis and they can mention the characteristics of helminthiasis 90.91% Women, 45.45% early elderly and 100% married. The number of respondents who have never used deworming medication is the same as the number of respondents who have used deworming medication, which is 46.9%. Meanwhile, the profile of respondents who have used deworming medication 93.33% are married, 80% are women, 40% are early adults. The conclusion is the community in Sungai Madang Village still have low knowledge about helminthiasis and the use of worm medicine.Keywords: knowledge level, helminthiasis, Sungai Madang, worm medicine